No longer supple? Molecular phylogeny suggests generic reassignment of Lygosoma ashwamedhi (Sharma, 1969) (Reptilia: Scincidae) - Srinivasulu, Chelmala; Srinivasulu, Bhargavi; Srinivasulu, Aditya; Seetharamaraju, Midathala (Zootaxa, 2016)
Morphometrics and phylogenetic analysis based on 12S and 16S ribosomal RNA (rRNA) gene sequences reveal that Riopa ashwamedhi Sharma, 1969 is placed incorrectly in the genus Riopa or Lygosoma, and we transfer this taxon to the genus Eutropis. New material of this rare and endemic species forms the basis of the generic reassignment. A detailed description of E. ashwamedhi (Sharma, 1969) comb. nov. and natural history notes are provided based on the new material collected in Andhra Pradesh, India.